The use of the smartphone in the teaching of photography in the blended modality from the point of view of Peruvian undergraduate teachers - Palacios-Fuentes, Kevin (2024)
The development of technology forces us to create new ways of teaching photography, to produce methods that allow students to combine the discourses of practical teaching with current aesthetic theory. Therefore, the objective of this research is to analyze how the use of smartphones facilitates the teaching of photography in blended mode according to the perceptions of teachers of the general photography workshop course at a private university in Lima, Peru. Its approach is qualitative, it is positioned in the interpretive paradigm and ethnographic design. Interviews were conducted with ten photography teachers in the blended mode of the general photography workshop course. From this, it was determined that the factors considered to facilitate the teaching of photography in blended mode are access to technology, immediacy of learning, ease of handling the Smartphone, portability and security.